1997
DOI: 10.1203/00006450-199712000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Functional Assay for Activated Protein C Resistance and Factor V Leiden in the Neonate

Abstract: A factor V506 Arg-Gln mutation is the most common inherited cause of thrombophilia in adults. To date, there are no data regarding the detection of this mutation in neonatal blood or the relationship of this dysfunctional factor V to neonatal thrombosis. This study compared a modified activated protein C resistance functional assay with the PCR-based DNA assay for the factor V mutation in 115 prospectively collected umbilical cord blood samples. The incidence of activated protein C resistance in cord blood was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The frequency of the factor V Leiden mutation in our general population is 6% as determined by analysis of 115 random cord blood samples. There was a 100% correlation between the factor V Leiden mutation and a modified n-APCR result below two standard deviations of the mean control value in that series [17]. The odds ratio for the factor V Leiden mutation in children with non-CNS venous thrombosis is 2.72 (95% confidence interval 1.34-5.53).…”
Section: Resultsmentioning
confidence: 64%
“…The frequency of the factor V Leiden mutation in our general population is 6% as determined by analysis of 115 random cord blood samples. There was a 100% correlation between the factor V Leiden mutation and a modified n-APCR result below two standard deviations of the mean control value in that series [17]. The odds ratio for the factor V Leiden mutation in children with non-CNS venous thrombosis is 2.72 (95% confidence interval 1.34-5.53).…”
Section: Resultsmentioning
confidence: 64%
“…Suitable proteinbased assays, i.e. APC-resistance [66,67], protein C activity, free and total protein S antigen, antithrombin activity, fibrinogen concentration, plasminogen activity, coagulation factors VIIIC and XII, lipoprotein (a) [68,69], and fasting homocysteine concentrations should be investigated along with DNA-based assays, i.e. factor V G1691A mutation, prothrombin G20210A variant and MTHFR C677T genotype.…”
Section: Screening Tests Time Point Of Testing and Interpretation Omentioning
confidence: 99%
“…It has been reported that cord plasma is more susceptible to the anticoagulant action of exogenous APC than adult venous blood, due to lower concentrations of AT and tissue factor pathway inhibitor [15]. However, Sifontes et al found no statistically significant difference between the APCR level of cord blood and venous blood of healthy adults without FVL mutation in a thromboplastin-based APCR assay [12]. In another study, the APCR ratio in cord blood was found to be higher (decrease in resistance to APC) than that in venous blood from children older than 6 months of age in an APTT-based APCR assay [16].…”
Section: Discussionmentioning
confidence: 96%
“…APCR can also occur in a number of acquired conditions with increased thrombosis risk such as pregnancy, preeclampsia, use of oral contraceptives, and increased factor VIII levels [9][10][11]. Although the APCR level in cord blood has been reported to be similar to that of adult venous blood [12], little information is available concerning its variations with pregnancy-and birth-related variables. The objectives of this study were to compare APCR levels in the cord blood of healthy newborns and in adult venous blood, and to investigate the effects of pregnancy-and birth-related variables to the levels of APCR in cord blood.…”
Section: Introductionmentioning
confidence: 96%